Pengaruh Fasilitas Kerja Terhadap Kinerja Personel Amc (Apron Movement Control) Dalam Plotting Parking Stand Di Bandar Udara Internasional Adi Soemarmo - Nadya Putri Ayu; Anita Nur Masyi’ah (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
, Apron Movement Control (AMC) is a unit in charge of monitoring traffic movements on the apron. Furthermore, to determine the effect of work facilities on the performance of AMC personnel in completing their duties. The research was conducted from 6 June 2022 to 31 July 2022 at the Apron Movement Control (AMC) unit at Adi Soemarmo International Airport. This research was conducted using a mixed methods research method, namely a combination of quantitative research methods which were then strengthened by qualitative methods. The results of this study indicate that work facilities affect the performance of AMC personnel in plotting aircraft parking stands at Adi Soemarmo International Airport. This can be seen from the value of the coefficient of determination (R square) based on the results of the analysis, R square is 85.2% and 14.8% influenced by variables or other factors outside the research that has been done by researchers.